Arka Vikram: An early, high-yielding hybrid of ridge gourd - Varalakshmi, B; Pitchaimuthu, M; Rao, E Sreenivas; Kumar, Sandeep; Jayanthi, P D Kamala; Raghupathy, H B; Mahesha, B; Nair, A K (Indian Horticulture, 2024)
Arka Vikram has been released and notified by the Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Horticultural Crops for cultivation in Zone IV (Punjab, Uttar Pradesh, Bihar and Jharkhand) and VIII (Karnataka, Tamil Nadu and Kerala) at National level. This is a very early hybrid, produces first female flower at 9th node in 40 days after sowing and takes 46 days for first picking. Fruits are green, long, tender, yields 29-42 t/ha in 120-135 days crop duration. The growers will be benefitted by this hybrid because of its early fruiting, better nutritional quality and yield.